THE IMPACT OF INTERNAL COMMUNICATION ON VIETNAMESE GEN Z EMPLOYEES’ WORK SATISFACTION - Ly-Le, Tuong-Minh; Phuong Le, Hanh Canh (Universitas Pelita Harapan, 2024)
This study aims to explore how effective internal communication influences the job satisfaction of Vietnamese Gen Z employees, and to understand whether good internal communication can enhance Gen Z employees’ comprehension of their job roles, promotion opportunities, relationships with supervisors, and co-worker interactions, ultimately leading to increased job satisfaction.The research comprises two phases: a pilot survey and in-depth interviews. The pilot survey confirmed the importance of internal communication and its perceived influence on job satisfaction. Subsequently, in-depth interviews provided nuanced insights into how internal communication practices affect their understanding of work nature, promotion opportunities, relationships with supervisors, and co-workers.The findings indicate that effective internal communication positively affects Gen Z employees’ understanding of their job roles, increases their awareness of training and promotion opportunities, enhances relationships with supervisors, and fosters productive co-worker interactions. While it did not directly influence salary levels, these internal communication efforts significantly improved job satisfaction. Abstrak dalam Bahasa Indonesia. Penelitian ini bertujuan untuk mengeksplorasi bagaimana komunikasi internal yang efektif mempengaruhi kepuasan kerja karyawan Gen Z di Vietnam, dan untuk memahami apakah komunikasi internal yang baik dapat meningkatkan pemahaman karyawan Gen Z tentang peran pekerjaan mereka, peluang promosi, hubungan dengan atasan, dan interaksi dengan rekan kerja, yang pada akhirnya meningkatkan kepuasan kerja. Penelitian ini terdiri dari dua fase: survei pendahuluan dan wawancara mendalam. Survei pendahuluan mengonfirmasi pentingnya komunikasi internal dan pengaruhnya terhadap kepuasan kerja yang dirasakan. Selanjutnya, wawancara mendalam memberikan wawasan yang lebih mendetail tentang bagaimana praktik komunikasi internal memengaruhi pemahaman mereka tentang sifat pekerjaan, peluang promosi, hubungan dengan atasan, dan rekan kerja. Temuan menunjukkan bahwa komunikasi internal yang efektif secara positif mempengaruhi pemahaman karyawan Gen Z tentang peran pekerjaan mereka, meningkatkan kesadaran mereka tentang peluang pelatihan dan promosi, memperbaiki hubungan dengan atasan, dan mendorong interaksi yang produktif dengan rekan kerja. Meskipun tidak secara langsung mempengaruhi tingkat gaji, upaya komunikasi internal ini secara signifikan meningkatkan kepuasan kerja.